Adoption of Novel Nano Bio-vascular Stent in Carotid Artery Stenosis Stent Intervention and Perioperative Nursing Analysis: Adoption of Novel Nano Bio-vascular Stent in Carotid Artery Stenosis Stent - Wan, Taihu; Jing, Tao; Zhang, Hongwei; Lan, Xiaoxue; Chen, Yahong (Cellular and Molecular Biology, 2022)
This work was developed to explore the adoption value of bacterial cellulose (BC) and heparin (He) combined with novel nano bio-vascular stents in carotid artery stent implantation, as well as the nursing methods and effects during the perioperative period. Based on the BC artificial blood vessel preparation method, the BC-He novel nano bio-vascular stent was fabricated after the modification of the medium method. Infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and X-ray electron diffraction (XRD) were performed to analyze the crystal structure and chemical structure of the material. In addition, scanning electron microscope (SEM) and transmission electron microscope (TEM) were employed to observe the micro-morphology of the stent. The mechanical properties and thermal stability of the materials were also characterized. Then, with 98 patients undergoing carotid artery stenting (CAS) as the research object, BC-He novel nano bio-vascular stent was applied to treat patients with arterial stenosis. According to different nursing methods, patients were assigned to the conventional nursing group (group A) and perioperative nursing group (group B). The postoperative complications, nursing effect, and satisfaction degree of the two groups were compared. It turned out that the BC-He novel nano bio-vascular stent was a kind of micro-mesh structure. There were characteristic absorption peaks of BC and He in BC-He, and there were N and S from He. Moreover, it also contained BC and He characteristic diffraction peaks, its tensile strength was significantly lower than BC, and its thermal stability was higher than BC. The preoperative carotid artery stenosis ranged from 50 % to 75 %, and the postoperative stenosis rate of restenosis patients treated with BC-He novel nano bio-vascular stent was less than 10 %. In addition, there were 92 patients (93.88 %) whose symptoms improved or markedly improved within 1 to 2 weeks after the operation, and 78 patients (79.6 %) had improved hemodynamic parameters. The incidence of postoperative complications in group A was dramatically superior to that in group B (P < 0.05). The total effective rate of nursing care and the degree of nursing satisfaction in group B were better than those in group A (P < 0.05). In short, BC-He novel nano bio-vascular stent had good mechanical properties and thermal stability, which was a safe and effective material for the treatment of carotid artery stenosis. In addition, the perioperative nursing method was effective and was of certain clinical adoption value.